ATTITUDE TO THE HISTORICAL AND CULTURAL HERITAGE OF THE PEOPLE - Yusupov Zafar Usmanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides a comparative analysis of the relationship of historical and cultural monuments of Uzbekistan to the Soviet dictatorship and years of independence based on archival materials, press materials, as well as scientific articles and brochures. Suggestions and comments on improving the industry are given.